Multiple emission bands NIR-persistent luminescence mSiO2@Zn0.6Ca0.4Ga2O4:Cr3+, Yb3+ nanoparticles for biological applications. Issue 4 (12th January 2021) - Lin, Yaling; Hu, Jie; Wu, Luyan; Zou, Qilin; Chen, Dejian; Huang, Decai; Lu, Hongyu; Wang, Shi-Bin; Zhu, Haomiao
Abstract : Synthesis of multiple emission bands NIR-persistent luminescence nanoparticles with regular morphology using mesoporous silica as a template. Abstract : Persistent luminescence nanoparticles (PLNPs) emitting in the NIR window (700–1700 nm) have shown great promise in the field of fluorescence imaging due to their unique properties, including the absence of in situ excitation and low optical scattering in tissues. However, they are still facing some challenges, such as irregular shape, wide size distribution and poor persistent luminescence performance. Here, we report a facile mesoporous template method for synthesizing mSiO2 @Zn0.6 Ca0.4 Ga2 O4 :Cr 3+, Yb 3+ (mSiO2 @ZCGO) persistent luminescent nanoparticles, which show a regular morphology and a size of about 69 nm. In addition, these nanocrystals exhibit persistent luminescence in multi-NIR windows, the first infrared window (∼696 nm of Cr 3+ emission) and second infrared window (∼1000 nm of Yb 3+ emission). Under illumination of a 254 nm UV lamp for 10 min, the persistent time of Cr 3+ ions and Yb 3+ ions lasted more than 120 min and 10 min, respectively. In particular, the NIR persistent emission of mSiO2 @ZCGO could be stimulated by soft X-ray, which is beneficial to long-term imaging in deep tissues. The optical penetration length of Yb 3+ ions persistent luminescence was evaluated to be 2.8 mm. These results demonstrate the great promise of mSiO2 @ZCGO for deep-tissue bio-imaging.